Factors associated with the increasing trend of contralateral prophylactic mastectomy among patients with ductal carcinoma in situ: Analysis of Surveillance, Epidemiology, and End Results data. (August 2018) - You, Qiuting; Chen, Kai; Li, Yudong; Lai, Jianguo; Fang, Yichao; Shen, Shiyu; Liu, Yicheng; Su, Fengxi; Yu, Fengyan
Abstract: Purpose: Our study aimed to investigate the factors influencing trends of contralateral prophylactic mastectomy (CPM) among patients with unilateral ductal carcinoma in situ (DCIS). Patients and Methods: We used the Surveillance, Epidemiology, and End Results (SEER) data to identify patients with unilateral DCIS diagnosed from 1998 to 2013. Patients were categorized as breast-conserving surgery (BCS), Unilateral Mastectomy and CPM group. Univariate and multivariate logistic regressions were applied to assess the factors associated with undergoing CPM among mastectomy patients. The trends of CPM among mastectomy patients through year were presented by different subgroups of sociodemographic and pathological characteristics. Results: Of those, 105326 patients with DCIS were identified, and 6370 patients underwent CPM. The proportion of CPM was 6.05% for all surgically-treated patients and 21.09% for mastectomy patients, and it increased more than six-fold between 1998 and 2013 (from 1.74% to 10.89% for all surgically-treated patients and from 5.44% to 37.47% for mastectomy patients). Younger age, white race, married status, smaller tumor size, positive ER and PR status were significantly associated with higher CPM proportion among mastectomy patients. The proportion of CPM was increasing through year, and the increasing trends were obvious in the subgroups of younger, white, married, metropolitan, with higher bachelor degree and higher median family income patients, while there were no apparent differences in the trends between subgroups of pathological characteristics. Conclusion: The trends of CPM among mastectomy patients were increasing through years and influenced by patients' sociodemographic characteristics, but not pathological characteristics. Highlights: Unilateral breast cancer patients tend to choose CPM year by year. Both tumors' and patients' factors were associated with the proportion of CPM. The increasing trend of CPM was influenced by sociodemographic characteristics.